The Constitutional Court Ultra Petita as a Protection Form of Economic Rights in Pancasila Justice - Abra, Emy Hajar; Wahanisa, Rofi (Faculty of Law, Universitas Negeri Semarang, 2020)
Social justice concept has been clearly emphasized at Pancasila (the five fundamental values of Indonesia) as one of common values of Indonesia society. Pancasila also recognized as the philosophical grondslag which makes Pancasila as a reference of all Indonesian citizens and State Action, including in governance. The concept of social justice in Pancasila implies that any natural resource management that has the potential to prosper and affect the Indonesian people as a whole must be controlled by the State as well as used for the greatest prosperity of the people. This paper is intended to analyze, describe, and examine the Constitutional Court Decision concerning to social justice especially in terms of economic rights. This paper discusses various decisions of the Constitutional Court that are ultra petita. This paper illuminated and highlighted that in two Constitutional Court Decisions on Water Resources and the Decision on the Electricity Law and the Water Resources Law of the Constitutional Court in its decision to make an ultra petita decision by canceling the entire two laws, because that the article being tested is the heart of the law, thus seriously affecting the implementation of other articles in the law. Therefore, with the ultra petita decision, in the future, the Constitutional Court is expected to be more progressive and responsive in seeing the problems that occur, especially related to the basic economic needs of the Indonesian people. Because the Constitutional Court is the guardian of the constitution whose main function is to maintain Indonesia's highest legal order (constitution).